The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jper.19-0351
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix‐based scaffolding technologies for periodontal and peri‐implant soft tissue regeneration

Abstract: The present article focuses on the properties and indications of scaffold‐based extracellular matrix (ECM) technologies as alternatives to autogenous soft tissue grafts for periodontal and peri‐implant plastic surgical reconstruction. The different processing methods for the creation of cell‐free constructs resulting in preservation of the extracellular matrices influence the characteristics and behavior of scaffolding biomaterials. The aim of this review is to discuss the properties, clinical application, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
141
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(168 citation statements)
references
References 69 publications
2
141
0
Order By: Relevance
“…Therefore, decellularized material, which is derived from growing cells, is a promising alternative. Only very few studies have described in vitro generated material for decellularization and most of them focused on periodontal tissue or blood vessel regeneration (Tavelli et al, 2019;Tondreau et al, 2015). Beside the material itself, the process of decellularization is also a critical step for decellularized tissue engineered material.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, decellularized material, which is derived from growing cells, is a promising alternative. Only very few studies have described in vitro generated material for decellularization and most of them focused on periodontal tissue or blood vessel regeneration (Tavelli et al, 2019;Tondreau et al, 2015). Beside the material itself, the process of decellularization is also a critical step for decellularized tissue engineered material.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine-derived acellular collagen scaffolds have been successfully introduced in the field of periodontal regenerative and implant surgery as a viable alternative to autogenous connective tissue grafts [ 2 , 3 , 6 ]. The collagenous structure of the regenerative matrices under investigation in the present study contains cellular binding and activation motifs, which are supposed to enhance the recruitment, attachment, and subsequent activation of oral cells with different phenotypes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical characteristics of the matrices can certainly affect their wound-healing properties [ 6 , 55 , 56 ]. A number of studies have demonstrated an impact of the matrix composition, porosity and pore size on the cellular attachment, proliferation, and motility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations